Listening to and believing derogatory and threatening voices - Sheaves, B (2023)
Background: An appraisal account has been important in understanding and treating the distress of people who hear voices. Over the past 25 years, a substantial body of research has accumulated that supports the view that appraisals concerning malevolence and omnipotence of voices have significant associations with voice-related distress. Each type of appraisal explains approximately a fifth of the variance in distress. Substantial variance in voice-related distress is therefore left unexplained. The aim of this thesis is to extend the appraisal account by focusing on one common presentation of voices: derogatory and threatening voices (DTVs). A cognitive framework is developed to understand a paradox: patients know that these voices intend to upset them, and yet they typically listen to and believe the threats and criticisms heard. Specifically, the objectives were to develop a grounded theory of reasons for listening to and believing DTVs, produce assessment measures to assess key constructs in the approach, test associations between listening to and believing DTVs and distress, and between the reasons and the degree of listening to and believing DTVs and lastly to develop an initial understanding of factors other than appraisals that might lead to greater listening to and believing DTVs.